Brand Image, Service Quality, and Online Customer Review on the Decision to Use Gojek Application Services in Pekanbaru - Amin, Amirudin M.; Utari, Veren Veronica; Tjahjana, Dominicus Josephus Swanto; Syahputra, Hidayat; S, Maulana Rezfajri (Interconnection: An Economic Perspective Horizon, 2023)
This study aims to determine and analyze the effect of brand image, service quality, and online customer reviews on purchasing decisions. The population of this study was students of the Pelita Indonesia Institute of Business and Technology, totaling 2,117 people with a sample size of 100 respondents. The sampling technique used was purposive sampling and proportionate stratified random sampling with the Slovin formula. The data analysis technique uses multiple linear regression analysis and hypothesis testing (t-test) with the help of the SPSS version 26 program. The results of this study indicate that brand image, service quality, and online customer review variables have a significant effect on the decision to use the Gojek application service in Pekanbaru (Case Study on Students of the Pelita Indonesia Institute of Business and Technology).